Creation of a Multidisciplinary Drug Use Endocarditis Treatment (DUET) Team: Initial Patient Characteristics, Outcomes, and Future Directions. (2nd March 2022) - Vyas, Darshali A; Marinacci, Lucas; Bearnot, Benjamin; Wakeman, Sarah E; Sundt, Thoralf M; Jassar, Arminder S; Triant, Virginia A; Nelson, Sandra B; Dudzinski, David M; Paras, Molly L
Abstract: Background: Consensus guidelines recommend multidisciplinary models to manage infective endocarditis, yet often do not address the unique challenges of treating people with drug use–associated infective endocarditis (DUA-IE). Our center is among the first to convene a Drug Use Endocarditis Treatment (DUET) team composed of specialists from Infectious Disease, Cardiothoracic Surgery, Cardiology, and Addiction Medicine. Methods: The objective of this study was to describe the demographics, infectious characteristics, and clinical outcomes of the first cohort of patients cared for by the DUET team. This was a retrospective chart review of patients referred to the DUET team between August 2018 and May 2020 with DUA-IE. Results: Fifty-seven patients were presented to the DUET team between August 2018 and May 2020. The cohort was young, with a median age of 35, and injected primarily opioids (82.5% heroin/fentanyl), cocaine (52.6%), and methamphetamine (15.8%). Overall, 14 individuals (24.6%) received cardiac surgery, and the remainder (75.4%) were managed with antimicrobial therapy alone. Nearly 65% of individuals were discharged on medication for opioid use disorder, though less than half (36.8%) were discharged with naloxone and only 1 patient was initiated on HIV pre-exposure prophylaxis. Overall, the cohort had a high rate of readmission (42.1%) within 90 days of discharge. Conclusions: Multidisciplinary care models such as the DUET team can help integrate nuanced decision-making from numerous subspecialties. They can also increase the uptake of addiction medicine and harm reduction tools, but further efforts are needed to integrate harm reduction strategies and improve follow-up in future iterations of the DUET team model.